Impact of dietary nitrate supplementation via beetroot juice on exercising muscle vascular control in rats - Ferguson, Scott Kohman (Kansas State University, 2012)
Introduction: Dietary nitrate(NO[subscript]3[superscript]-) supplementation, via its reduction to nitrite (NO [subscript] 2 [superscript]-) and subsequent conversion to nitric oxide (NO) and other reactive nitrogen intermediates, reduces blood pressure and the O[subscript]2 cost of submaximal exercise in humans. Despite these observations, the effects of dietary NO [subscript]3 [superscript]- supplementation on skeletal muscle vascular control during locomotory exercise remain unknown. We tested the hypotheses that dietary NO [subscript]3 [superscript]- supplementation via beetroot juice (BR) would reduce mean arterial pressure (MAP) and increase hindlimb muscle blood flow in the exercising rat. Methods: Male Sprague-Dawley rats (3-6 months) were administered either NO [subscript]3 [superscript]- (via beetroot juice; 1 mmol · kg[superscript]-[superscript]1 · day[superscript]-[superscript]1, BR n=8) or untreated (control, n=11) tap water for 5 days. MAP and hindlimb skeletal muscle blood flow and vascular conductance (radiolabeled microsphere infusions) were measured during submaximal treadmill running (20 m · min[superscript]-[superscript]1, 5% grade). Results: BR resulted in significantly lower exercising MAP (control: 137 ± 3, BR: 127 ± 4 mmHg, P<0.05) and blood [lactate] (control: 2.6 ± 0.3, BR: 1.9 ± 0.2 mM, P<0.05) compared to control. Total exercising hindlimb skeletal muscle blood flow (control: 108 ± 8, BR: 150 ± 11 ml · min[superscript]-[superscript]1 · 100 g[superscript]-[superscript]1, P<0.05) and vascular conductance (control: 0.78 ± 0.05, BR: 1.16 ± 0.10 ml · min[superscript]-[superscript]1 · 100 g[superscript]-[superscript]1 · mmHg[superscript]-[superscript]1, P<0.05) were greater in rats that received beetroot juice compared to control. The relative differences in blood flow and vascular conductance for the 28 individual hindlimb muscles and muscle parts correlated positively with their percent type IIb + d/x muscle fibers (blood flow: r=0.74, vascular conductance: r=0.71, P<0.01 for both). Conclusion: These data support the hypothesis that NO [subscript]3 [superscript]- supplementation improves vascular control and elevates skeletal muscle O [subscript]2 delivery during exercise predominantly in fast-twitch type II muscles, and provide a potential mechanism by which NO [subscript]3 [superscript]- supplementation improves metabolic control.
Keywords: Nitric Oxide; Blood flow; Dietary; Nitrate; Physiology (0719)